2019
DOI: 10.1371/journal.pone.0214744
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioactive compounds with bactericidal and antioxidant potential by endophytic fungus Alternaria alternata AE1 isolated from Azadirachta indica A. Juss.

Abstract: For combating multidrug-resistant microorganisms, exploration of natural compounds from plant endophytes increases the chance of finding novel compounds. An efficient bioactive metabolites producing endophytic fungal strain AE1 was isolated from leaves of Azadirachta indica A. Juss. The metabolites were found to be thermostable, non-proteinacious and produced prominent zones of inhibition against numbers of Gram positive and Gram negative bacteria. Based on 28S rDNA (D1/D2) sequence homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 36 publications
2
39
0
1
Order By: Relevance
“…They also confirmed that the treated cells were lost their shape and integrity followed by the ultimate cell death. Besides, Chatterjee 58 reported some deformations and prominent degradation of cell wall structures were observed on Escherichia coli, and Salmonella Typhimurium exposed to the extract of Alternaria alternata AE1, a fungal endophyte from Azadirachta indica. They also observed end-to-end joining of bacterial cells upon treatment indicating an effect of antimicrobial agents on normal cell division function and presumed that the massive distortion of morphological structures of bacteria cells may be due to the mode of action of antimicrobial agents on the bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…They also confirmed that the treated cells were lost their shape and integrity followed by the ultimate cell death. Besides, Chatterjee 58 reported some deformations and prominent degradation of cell wall structures were observed on Escherichia coli, and Salmonella Typhimurium exposed to the extract of Alternaria alternata AE1, a fungal endophyte from Azadirachta indica. They also observed end-to-end joining of bacterial cells upon treatment indicating an effect of antimicrobial agents on normal cell division function and presumed that the massive distortion of morphological structures of bacteria cells may be due to the mode of action of antimicrobial agents on the bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…However, endophytic fungi from genus Aspergillus have been stated as a source of bioactive secondary metabolites having diverse applications [36,37,38]. Bioactive metabolites derived from endophytic fungi revealed antimicrobial activity against a variety of organisms [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endophytic fungi are not counted as saprophytes since they are related to living tissues and may participate in the wellbeing of the plant [10]. These fungi have been identified as useful sources of bioactive secondary metabolites and many of them have the ability to produce antimicrobial substances [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…which also possesses antipathogenic activities [368]. Recently, Chatterjee et al [369] identified the metabolites produced by Alternaria alternata isolated from A. indica showing inhibitory activities against Gram-negative and Gram-positive bacteria. The highly functionalized antibacterial naphthaquinone, javanicin (15), has been reported from an endophytic fungus Chloridium sp.…”
Section: Bioactive Natural Compounds Of Endophytic Fungi Isolated Fromentioning
confidence: 99%